The Meaning of Human Resources Management an a Corporation: A Theoretical Perspective - Dasmadi (Enrichment : Journal of Management, 2022)
This study was aims to exatly determine the meaning and the role of human resource management in corporation aor in a organization. We used the method of qualitative approach with the way of literature review (library research) and basicly empirical research too. As we knew , that from the discussion it can be concluded that human resource management is the tactical point with the meaningfull role and talk managing human resources effectively. So the all the resources that available in the corporation or organization, all of us knew that human resources are very very important and also very very decisive. As you knew, the all of a potential possessed by human resources greatly influences the organization's efforts to achieve its goals.